2017
DOI: 10.1007/s10040-016-1519-3
|View full text |Cite
|
Sign up to set email alerts
|

The World Karst Aquifer Mapping project: concept, mapping procedure and map of Europe

Abstract: Karst aquifers contribute substantially to freshwater supplies in many regions of the world, but are vulnerable to contamination and difficult to manage because of their unique hydrogeological characteristics. Many karst systems are hydraulically connected over wide areas and require transboundary exploration, protection and management. In order to obtain a better global overview of karst aquifers, to create a basis for sustainable international water-resources management, and to increase the awareness in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
152
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(183 citation statements)
references
References 27 publications
4
152
0
Order By: Relevance
“…Simplifying assumptions in the water budget calculation also contribute to uncertainties. Our estimates of fresh SGD are likely low under several conditions: (1) in layered unconfined‐confined aquifer systems, where a fraction of fresh SGD originates from deeper confined aquifers with more distal recharge zones; (2) in dry coastal regions which tend to receive groundwater import from upland basins (Schaller & Fan, ); (3) in karst, which represents 10% of the world's aquifers (Chen et al, ) and has complex patterns of recharge and conduit flow. Our estimates are likely high under other conditions: (1) in areas where groundwater discharges to unmapped tidal creeks or nearshore wetlands (this discharge is generally not considered “submarine” (Taniguchi et al, ), but is included with fresh SGD in the water budget method) and (2) in areas of intense groundwater extraction, which deducts from fresh SGD but can also enhance recharge.…”
Section: Methodsmentioning
confidence: 99%
“…Simplifying assumptions in the water budget calculation also contribute to uncertainties. Our estimates of fresh SGD are likely low under several conditions: (1) in layered unconfined‐confined aquifer systems, where a fraction of fresh SGD originates from deeper confined aquifers with more distal recharge zones; (2) in dry coastal regions which tend to receive groundwater import from upland basins (Schaller & Fan, ); (3) in karst, which represents 10% of the world's aquifers (Chen et al, ) and has complex patterns of recharge and conduit flow. Our estimates are likely high under other conditions: (1) in areas where groundwater discharges to unmapped tidal creeks or nearshore wetlands (this discharge is generally not considered “submarine” (Taniguchi et al, ), but is included with fresh SGD in the water budget method) and (2) in areas of intense groundwater extraction, which deducts from fresh SGD but can also enhance recharge.…”
Section: Methodsmentioning
confidence: 99%
“…Further, climate reconstructions are essential in understanding ecological and biogeographical responses to past hydrologic change in regions such as the Amazon rainforest, Pantanal, caatinga (Brazilian savannah), Cerrado, and Atlantic forests, which are among the regions with the richest biodiversity on Earth. [6]). Green triangles indicate study sites in the region identified by the Speleothem Isotopes Synthesis and Analysis (SISAL) working group but not included in the current version of the database, while purple circles show sites that are already in SISAL_v1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Water from these karst areas contributes significantly to the water supply of many countries. In Austria, 25% of the land surface is covered by carbonate rocks (Chen et al, ), and over 50% of the population, including large cities, such as Vienna, Salzburg, and Innsbruck, depend on drinking water from karst aquifers (Kralik, ). In view of increasing water demand, high alpine karst aquifers in particular offer an enormous potential for future water supply.…”
Section: Introductionmentioning
confidence: 99%